Pengaruh Diameter dan Konsentrasi Stimulansi Asam Cuka (C2H4O2) Terhadap Produktivitas Getah Pinus (Pinus merkusii Jungh et de Vriese) - Juki Pimroi Hutabalian Hutabalian; Ridwanti Batubara; Afifuddin Dalimunthe (Peronema Forestry Science Journal, 2015)
The Production of oleoresin is affected by the find out of stimulant and effect of diameter. The purpose of this research were to know the effect of C2H4O2 stimulant and effect of diameter to P. merkusii and to know the C2H4O2 concentration and the best of diameter. This research were carried at working area of PT. Inhutani IV, Siborong-borong in Maret – April 2014 using factorial randomized block design with two factors, i.e. the concentration of stimulant (0%, 10%, 20% and 30%) and diameter (25-30 cm, 31-35 cm, 36-40 cm and 41-45 cm). Parameter measured were production of oleoresin (gram). Result of this research showed that the application of C2H4O2 stimulant on the tapping of pine trees increase considerably to oleoresin. The application of C2H4O2 resulted in more than 2 – 4 times the yield of oleoresin from tree without stimulant. The concentration of C2H4O2 (30%) and the diameter 41-45 cm can gave the best product of oleoresin.The lowest sap production is 10.12 gram in each tree per a mounth and the highest production is 176.30 gram in each tree per a mounth.Key word : Pinus merkusii, Resin, Stimulant, Diameter